Developing house types & core house design by understanding house form & transformation processes in user-designed (SLUM) settlement - Pafin, Shem A.; Villaseca, Maria Rallah P. (2014)
Applying Rapoport?s concept on informal settlement considered as vernacular design, the proponent shall undergo a study regarding the user-designed slum settlement in the local scenes of Davao City. The study shall focus on the built environment and the process aspects including documentations and analysis, at the same time developing house forms and types and obtaining practical solutions ad lessons made by the settlers themselves. In a general sense, the proponent wants to know and unto what extent the people in this kind of environment would exercise their freedom upon building their shelter and lives. For given various constraints, how do the users create or improve their housing, with such limited materials? What are the processes made towards an ideal life, aspiration to new things, and how they are able to experience shelter in its simplest meaning. The study shall try to answer those questions, with regards to house forms and types and the occurring variables that affect transformation process and their complex relationships.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2014